J. Mayone Stycos. (comp.), Clinics, Contraception and Communication, Nueva York, N.Y., Meredith Corporation, 1973. 207 p. - Porras Macías, Agustín (Estudios Demográficos y Urbanos, 1973)
J. MAYONE STYCOS (Comp.), Clinics, Contraception and Communication, Nueva York, Meredith Corporation, 1973.